2000
DOI: 10.1093/arclin/15.6.495
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Cognitive Decline During Normal Aging: The Complex Effect of Education

Abstract: The purpose of this study was to further analyze the effects of education on cognitive decline during normal aging. An 806-subject sample was taken from five different Mexican regions. Participants ranged in age from 16 to 85 years. Subjects were grouped into four educational levels: illiterate, 1-4, 5-9, and 10 or more years of education, and four age ranges: 16-30, 31-50, 51-65, and 66-85 years. A brief neuropsychological test battery (NEUROPSI), standardized and normalized in Spanish, was administered. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
111
0
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 0 publications
17
111
0
22
Order By: Relevance
“…The neuropsychological assessment consisted of tests of Attention (Trail Making Test Part A and Letter A Cancelation including Hits and Time in seconds as the dependent variables for both tests), Memory (Memory for three Phrases, Word List including Immediate recall, Delayed recall and Recognition, and recall of the Complex Figure of Rey), Language (Phonological Fluency – Letter FAS and Boston naming test), Constructional Praxis (Copy of the Complex Figure of Rey), and Executive Functions (Wisconsin Card Sorting Test including Hits, Number of Categories and Conceptualization, and the Semantic Fluency Test – Animals). For a more detailed description of these tests and the Spanish norms see Ardila et al (1994, 2000). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The neuropsychological assessment consisted of tests of Attention (Trail Making Test Part A and Letter A Cancelation including Hits and Time in seconds as the dependent variables for both tests), Memory (Memory for three Phrases, Word List including Immediate recall, Delayed recall and Recognition, and recall of the Complex Figure of Rey), Language (Phonological Fluency – Letter FAS and Boston naming test), Constructional Praxis (Copy of the Complex Figure of Rey), and Executive Functions (Wisconsin Card Sorting Test including Hits, Number of Categories and Conceptualization, and the Semantic Fluency Test – Animals). For a more detailed description of these tests and the Spanish norms see Ardila et al (1994, 2000). …”
Section: Methodsmentioning
confidence: 99%
“… *Could not complete the assessment; Cut-off values: were obtained from the norms corresponding to the same population (Ardila et al, 1994, 2000); Lawton: Scale of Instrumental Activities of Daily Living (IADL) . The P300 variables collected during the first assessment and the Neuropsychological variables collected during the second assessment are presented. In order to assist in the clinical decision, the neuropsychological data from the first and second assessment were contrasted.…”
Section: Table A1mentioning
confidence: 99%
See 1 more Smart Citation
“…However, decline in cognitive domains is not uniform across all individuals, and even in the same individual, throughout aging (Riddle, 2007). For instance, factors that can possibly confer a risk of decline in cognitive performance, other than age in itself, are low(er) level of schooling, institutionalization, female gender, depressive mood, and the presence of “unhealthy” lifestyle factors and/or of clinical pathologies (Ardila et al, 2000; Van Gool et al, 2003, 2007; Wilson et al, 2009; Yamamoto et al, 2009; Paulo et al, 2011; Köhler et al, 2012; Santos et al, 2012; Costa et al, 2013; Viscogliosi et al, 2013). This heterogeneity in cognitive aging, and the need to reach larger population samples, challenges the available instruments that currently exist to efficiently assess global cognition and screen/detect deviations from healthy (“normal”) cognitive aging to cognitive impairments and dementia.…”
Section: Overviewmentioning
confidence: 99%
“…Another factor may be associated with the negative effect of age on lexical retrieval (Mansur, Radanovic, Rüegg, Mendonça, & Scaff, 2002;Obler, Au, & Albert, 1995;Taylor & Burke, 2002) and on inhibitory functions . However, age and education may act alone or in different forms of interaction, which suggests the existence of a complex effect between these variables, which may depend on the cognitive domain under study (Ardilla, Ostrosky-Solis, Rosselli, & Gomez, 2000). Studies using VFTs showed that education may play a role on the effect of age: (a) older people with a high educational level had a better performance when different task criteria were adopted than older people with an intermediate or low educational level (Henry & Phillips, 2006); (b) adults produced more words than older individuals only in the groups with up to four years of schooling (Rodrigues et al, 2008); and (c) people about 70 years old and a high educational level had a performance that was similar to young people about 20 years old with a low educational level (Federmeier et al, 2002).…”
mentioning
confidence: 99%